PENGELOLAAN ASET TETAP TANAH DAN BANGUNAN DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH DI KOTA GORONTALO - Elsa Alvionita; Yanti Aneta; Rustam Tohopi (stiatabalong.ac.id, 2023)
This study aims to determine the management of Land and Building Fixed Assets in increasing Gorontalo City Local Revenue in terms of planning, implementation and supervision, and to determine the factors that determine asset management in terms of asset management flow which includes asset inventory, valuation and legal audit. Data collection techniques were carried out by observation, documentation and interviews with 4 main informants. Data analysis techniques use data reduction, data presentation and conclusions. The findings of the study show that in the management of fixed assets of land and buildings in increasing the original income of the Gorontalo city area both in planning, implementation and supervision has basically been carried out but has not run well because there are still obstacles in utilization, namely obstacles in assessing assets to obtain fair value. The lack of government appraisers is an obstacle in utilization so that it can affect local original income and Factors that determine the management of Land and Building Fixed Assets in Increasing Local Original Income of Gorontalo City seen from the flow of asset management which includes asset inventory, valuation and Legal audit, have not been carried out properly because in the assessment process there are still obstacles, namely the lack of appraisers from the government and in the Legal audit There are several processes that have not been carried out in accordance with the guidelines used by the Gorontalo City Finance Agency such as there are still government-owned land assets that do not have proof of ownership. This is shown by the absence of SOPs on regional asset management at the Gorontalo City Finance Agency as stated in Permendagri No. 19 of 2016.